Austrodiplostomum compactum (Lutz, 1928) (Digenea, Diplostomidae) in the eyes of fishes from Paraná river, Brazil - doi: 10.4025/actascibiolsci.v34i2.9337 - Santos, Rosemeire de Souza; Marchiori, Natalia; Santarem, Vamilton Alvares; Takahashi, Haroldo Kazuyuki; Mourino, José Luis Pedreira; Martins, Maurício Laterça (Acta Scientiarum. Biological Sciences, 2011)
Parasitological indexes of Austrodiplostomum compactum (Digenea, Diplostomidae) in fishes from the Paraná River, Presidente Epitácio region, state of São Paulo, Brazil, and their relationship with climate and water quality are evaluated. Fifty-one specimens of Plagioscion squamosissimus, 39 Geophagus surinamensis, 27 Hoplias malabaricus and 23 Cichla sp. were collected between June 2007 and June 2008. Water quality and rainfall indexes were measured monthly. P. squamosissimus had the highest parasite rate, with 98% total prevalence, intensity of infection varying between 1 and 255 and parasite mean abundance totaling 40.5 ± 9.9. H. malabaricus had the next parasite rate, with 66.6% total prevalence, parasite intensity between 2 and 184 and mean abundance totaling 22.4 ± 20.9. Cichla sp. had a total prevalence of 52.1%, intensity between 1 and 21, and mean abundance 4.3 ± 2.9. Finally, G. surinamensis had a total prevalence of 46.1%, intensity between 1 and 53 and mean abundance 7.1 ± 8.8. A survey of diplostomid infection in Brazil and the role of piscivore fish as an important host have also been discussed.